2000
DOI: 10.1007/s002399910017
|View full text |Cite
|
Sign up to set email alerts
|

Concerted Evolution of a Highly Repetitive DNA Family in Eptatretidae (Cyclostomata, Agnatha) Implies Specifically Differential Homogenization and Amplification Events in Their Germ Cells

Abstract: In eight hagfish species, it is known that chromosome elimination occurs during early embryogenesis, and some highly repetitive DNA families, restricted to germ cells, have been isolated. One of these families, "EEEo2," has been isolated as DNA fragments by restriction enzyme analyses from Eptatretus okinoseanus and E. cirrhatus. In this study, EEEo2 sequences were isolated from germline DNA in E. burgeri, Paramyxine sheni, and P. atami using PCR methods. Sequence analysis revealed that these sequences are int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(52 citation statements)
references
References 35 publications
3
49
0
Order By: Relevance
“…In this species, more than 70% of the total DNA is expelled from presumptive somatic cells (Shichiri et al 1997). Two eliminated elements, EEEo2 and EEEb2, were previously detected as major and minor components of eliminated DNA, respectively (Nabeyama et al 2000;Kubota et al 2001). In this study, we identified four additional repetitive DNA elements accumulated as eliminated materials in P. sheni, designated EEPs1 to EEPs4.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…In this species, more than 70% of the total DNA is expelled from presumptive somatic cells (Shichiri et al 1997). Two eliminated elements, EEEo2 and EEEb2, were previously detected as major and minor components of eliminated DNA, respectively (Nabeyama et al 2000;Kubota et al 2001). In this study, we identified four additional repetitive DNA elements accumulated as eliminated materials in P. sheni, designated EEPs1 to EEPs4.…”
Section: Introductionmentioning
confidence: 94%
“…Slot blots were obtained by spotting a dilution series of denatured DNAs on membrane filters (GeneScreen Plus, DuPont/NEN Research Products) for subsequent hybridization under a procedure described previously (Nabeyama et al 2000). The 3′-or 5′-end DIG-labeled oligonucleotide probes were prepared for this study.…”
Section: Estimation Of Copy Numbermentioning
confidence: 99%
See 1 more Smart Citation
“…For example, it has been reported for all hagfish investigated that predetermined chromosomes and DNA fragments are eliminated during a stage of cell division in somatic cells, but not in germ-line cells. The phenomenon, called chromosomal elimination, has not been observed in any other vertebrates (Kohno et al, 1986;Kubota et al, 1992Kubota et al, , 1993Kubota et al, , 1997Kubota et al, , 2001Kohno, 1998;Nabeyama et al, 2000;Kloc and Zagrodzinska, 2001). The functions, roles, mechanisms, and evolutionary origin of this strange phenomenon are unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Current research focuses on their structural and functional relevance (Koch 2000;Lee et al 2000), the underlying evolutionary processes (Lee et al 1997;Nabeyama et al 2000) and their use as taxonomic (King and Cummings 1997;Fedorov et al 1999) and phylogenetic markers (Árnason et al 1992;Garrido-Ramos et al 1999). Available data are mostly sequences for single, i.e., monomeric units.…”
Section: Introductionmentioning
confidence: 99%